Factors Associated with Young Adults’ Career Information Seeking Behaviour and Sources of Information - Supeno, Eddy; Bourdon, Sylvain; Lapointe-Garant, Marie-Pierre (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2025)
Although research shows that information sources play an important role in career choice, few studies investigate the career information seeking behaviour of young adults with a multivariate approach of factors associated with the choice of information sources. This study is aimed at identifying the factors associated with young adults’ career information seeking behaviour in a sample of 1,400 young adults in the province of Quebec, and the information sources they used when collecting information on jobs, career possibilities, further education or training. Results show that more than half of respondents consulted two sources or more and that the most used information sources are personal relationships and educational institutions. The discussion highlights that young adults actively seek information regardless of their school attendance status. It underscores the importance of close relationships—such as family and friends—as key sources of information, and calls for tailored strategies to disseminate information that reflect the diverse needs and characteristics of different groups of young adults.